A Snapshot of Health Equity in Papua New Guinea : An Analysis of the 2010 Household Income and Expenditure Survey - Irava, Wayne; Barker, Katie; Somanathan, Aparnaa; Hou, Xiaohui (World Bank, Washington, DC, 2015)
In Papua New Guinea the poorest quintile is most vulnerable to illness, yet has the lowest utilization rates of healthcare facilities. When looking at age groups the elderly ( 55) are the most vulnerable to illness and the least likely to seek treatment. The lack of healthcare workers and the distance to facilities are among the most dominant reasons cited for not utilizing heath care in the poorest quintile. The perceived quality of services is a barrier to health care utilization across all quintiles. Out-of-pocket (OOP) payments have minimal catastrophic impact, yet have been found to still be a barrier to utilization - especially amongst the poorest quintile. The government should focus on and prioritize strengthening the health services delivery to achieve universal health coverage.